Beyond the Consumer Lens: Mapping Firm-Side Digital Marketing Studies in Indonesian MSMEs - Tindi, Ricardo Gianluigi; Silaban , Daniel Peterson (International Journal Administration, Business & Organization, 2025)
This study systematically reviews recent research on how Indonesian micro, small, and medium enterprises (MSMEs) adopt and use digital marketing in response to rapid digital transformation following the COVID-19 pandemic. Although digital marketing has emerged as a key driver for market visibility and customer engagement, many MSMEs still face challenges in integrating digital initiatives into strategic business processes. Using a dual-corpus design that combines Scopus-indexed and SINTA-indexed articles published between 2020 and 2025, this study maps how firm-side digital marketing research has developed in Indonesia, focusing on thematic patterns, methodological approaches, theoretical perspectives, and analytical levels. The findings indicate that existing research is concentrated on technology adoption and platform-based usage, while studies on capability development, system integration, and ecosystem support remain limited. Emerging topics include sustainability, digital innovation, and artificial intelligence, but these areas require deeper empirical grounding. This review highlights the need for multi-level research that connects individual behavior, organizational capabilities, and institutional environments to support long-term digital transformation among Indonesian MSMEs.